On impulsive Sturm–Liouville operators with singularity and spectral parameter in boundary conditions - Amirov, R.Kh.; Guldu, Y.; Topsakal, N. (Український математичний журнал, 2012)
We study properties and the asymptotic behavior of spectral characteristics for a class of singular Sturm–Liouville differential operators with discontinuity conditions and an eigenparameter in boundary conditions. We also determine theWeyl function for this problem and prove uniqueness theorems for a solution of the inverse problem corresponding to this function and spectral data. Дослiджено властивостi та асимптотичну поведiнку спектральних характеристик для класу сингулярних диференцiальних операторiв Штурма – Лiувiлля з розривними умовами та власним параметром у граничних умовах. Визначено функцiю Вейля для цiєї задачi та доведено теореми про єдинiсть розв’язку оберненої задачi, що вiдповiдає цiй функцiї та спектральним даним.